Association of benign joint hypermobility syndrome in children with mitral valve prolapse - Eman Gamal Abdelrahman; Ghada Saad Abdelmotaleb; Mohammed Rabee Abouelmaaty Hassane; Enas Mohammed Nor El-Deen (Egyptian Pediatric Association Gazette)
Abstract Background Mitral valve prolapse (MVP) is a frequently encountered valvular condition, estimated to affect approximately 2–3% of the general population, and is frequently associated with underlying connective tissue disorders. Benign joint hypermobility syndrome (BJHS) involves pronounced ligamentous laxity and is thought to exhibit overlapping pathophysiological features with MVP. This study aims to evaluate the association between BJHS and MVP in children. Methods In this case–control study, 50 children with MVP and 50 demographically matched controls were evaluated. All participants underwent a detailed clinical examination, Beighton hypermobility scoring, Brighton criteria assessment, and echocardiography. Results MVP patients had significantly higher Beighton scores (4.1 ± 2.1 vs. 2 ± 1.9, p < 0.001), with BJHS more frequent in the MVP group (38% vs. 10%, p < 0.001). Children with BJHS exhibited higher left ventricular internal diameter in diastole (LVIDd: 41.4 ± 6.8 vs. 36.4 ± 4.6 mm, p < 0.001) and left atrial diameter (LAD: 26.8 ± 5.1 vs. 23.9 ± 5.3 mm, p = 0.018). Classic and non-classic MVP were substantially more prevalent in BJHS patients (p = 0.007, respectively). Beighton score positively correlated with LVIDd (r = 0.447, p < 0.001) and LAD (r = 0.266, p < 0.001). Conclusions BJHS was significantly associated with MVP in children, with higher MVP severity and cardiac dimensions in hypermobile individuals.